Correction: Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)

Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)
Terrestrial and marine species are exhibiting distributional shifts due to climate change and resource availability. As food webs are impacted, some species have moved into areas of increased human activity, encountering anthropogenic hazards. A coastal marine species that undertakes a long migration between breeding and foraging ranges, the Eastern North Pacific (ENP) population of gray whales ( Eschrichtius robustus ) is especially vulnerable to changes. Subgroups of ENP gray whales, including the Pacific Coast Feeding Group and the (Puget) Sounders, have adapted to exploit alternative feeding grounds as prey availability declines in the Arctic. Novel to known migration phenology, gray whales have been observed seasonally since 2018 in San Francisco Bay (SF Bay), California. We evaluated subgroup identity and mortality of gray whales in SF Bay from 2018–2025 using photo-identification. Data were collected through vessel-based surveys, opportunistic effort, and community submissions. We identified 114 individual whales of which eight were matched to a subgroup, indicating gray whales utilizing SF Bay are not merely a range extension by foraging subgroups. Only four gray whales were resighted within SF Bay between years. Using photographs, 21 individuals were successfully matched to carcasses and a minimum mortality rate of 18% was determined. Blunt and/or sharp force trauma consistent with vessel strike was determined to be the cause of death for 30 of 70 carcasses, and for nine of 11 matched animals where a cause of death was determined. Sounder and PCFG matched whales were more likely to survive SF Bay than ENP individuals, though minimum length of stay did not influence mortality. This work confirms that gray whales entering SF Bay are highly susceptible to vessel strike mortality and highlights a crucial need to identify and implement adaptive management strategies to mitigate injuries and mortality as whales continue to utilize novel habitat.

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Stejneger's beaked whale strandings in Alaska, 1995–2020 - Katharine N. Savage; Kathy Burek‐Huntington; Sadie K. Wright; Anna L. Bryan; Gay Sheffield; Marc Webber; Raphaela Stimmelmayr; Pam Tuomi; Martha A. Delaney; William Walker (Marine Mammal Science, 2021)
Presented here is the first comprehensive and updated compilation of history, distribution, and findings of Stejneger's beaked whales ( Mesoplodon stejnegeri ) in Alaska. Stejneger's beaked whales are a poorly understood, elusive, deep‐diving cetacean species found in the North Pacific Ocean. Since Stejneger's beaked whale strandings data in Alaska through 1994 were last published, 35 additional strandings have been documented. Twenty‐seven animals stranded in the Aleutian Islands, seven stranded in Southcentral Alaska, and one animal stranded on St. Lawrence Island. Twenty‐two carcasses were necropsied, but only four were fresh. Seventeen of the 22 died during mass stranding events and cause of death could not be definitively determined. Barotrauma was suspected in three cases and infectious disease possibly complicated by barotrauma occurred in two cases. We documented an expansion of strandings into the northern Bering Sea, characterized a sex bias, examined stomach contents that included macroplastic, and identified parasites not previously associated with Stejneger's beaked whales. Also included are data on the largest known mass stranding of Stejneger's beaked whales, which occurred on Adak Island in 2018. The history, distribution, and findings presented here are central to further our understanding of this species.

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Prey-Related Asphyxiation in Harbor Porpoises (Phocoena phocoena) along the U.S. West Coast: Importance of American Shad (Alosa sapidissima) on Adult Female Harbor Porpoise Mortality - Cindy R. Elliser; John Calambokidis; Dalin N. D’Alessandro; Deborah A. Duffield; Jessica L. Huggins; James Rice; Isidore Szczepaniak; Marc Webber (Oceans, 2020)
Harbor porpoise (Phocoena phocoena) diets are predominantly comprised of small fish species (<30 cm) and squid. However, predation on larger species (up to 63 cm) occurs, raising the question of increased risk of asphyxiation associated with this behavior. Literature was reviewed and stranding data from 1983 to 2020 from the U.S. West Coast (including California, Oregon and Washington) were searched for cases of prey-related asphyxiation of harbor porpoises and analyzed in relation to age, sex, reproductive status and prey species. Twenty-nine cases were documented. Twenty-seven cases involved large prey; non-native American shad caused the asphyxiation in 87% of the cases where the prey species was identified. The majority (92%) of harbor porpoises were females, and at least 83.3% were pregnant or recently post-partum. Reproductively active females may be more likely to attempt potentially risky behavior in order to compensate for their increased energetic needs. Increasing numbers of non-native American shad may pose a unique danger in this region for harbor porpoises not adapted to deal with the challenges of that prey. This may be a cause for concern, as there is likely an interaction between location, age and reproductive status on the diet composition and foraging strategies of harbor porpoises.

Color patterns in white‐beaked dolphins ( Lagenorhynchus albirostris ) from Iceland - Chiara G. Bertulli; Anders Galatius; Carl C. Kinze; Marianne H. Rasmussen; William Keener; Marc A. Webber (Marine Mammal Science, 2016)
Few studies have examined the natural complex pigmentation patterns of white‐beaked dolphins. From 2002 to 2014, whale‐watching trips in Iceland provided a platform of opportunity to collect a large body of photographs of free‐ranging individuals from a single area of distribution for this species. Based on 823 images, 571 individuals showing one or more color components were identified, and assigned to the following four age classes: adults ( n = 437), juveniles ( n = 109), calves ( n = 14), and neonates ( n = 11). A total of 26 color components were observed and described: seven terms previously applied to white‐beaked dolphins, 12 previously applied to other dolphin species, and seven newly defined terms. Results showed that each age class could be positively identified by differences in specific color components, some of which were exclusive. Therefore, color patterns may prove useful in estimating maturity in free‐ranging white‐beaked dolphins. This tool could be further refined through assessment of a wide sample of freshly stranded specimens of known sex and age, which could reveal new age class‐specific components, as well as sexually dimorphic characteristics not seen here. Geographic variation should be investigated by comparing image data sets and stranded animals from different parts of the North Atlantic.

Estimation of walrus populations on sea ice with infrared imagery and aerial photography - Mark S. Udevitz; Douglas M. Burn; Marc A. Webber (Marine Mammal Science, 2008)
Population sizes of ice‐associated pinnipeds have often been estimated with visual or photographic aerial surveys, but these methods require relatively slow speeds and low altitudes, limiting the area they can cover. Recent developments in infrared imagery and its integration with digital photography could allow substantially larger areas to be surveyed and more accurate enumeration of individuals, thereby solving major problems with previous survey methods. We conducted a trial survey in April 2003 to estimate the number of Pacific walruses ( Odobenus rosmarus divergens ) hauled out on sea ice around St. Lawrence Island, Alaska. The survey used high altitude infrared imagery to detect groups of walruses on strip transects. Low altitude digital photography was used to determine the number of walruses in a sample of detected groups and calibrate the infrared imagery for estimating the total number of walruses. We propose a survey design incorporating this approach with satellite radio telemetry to estimate the proportion of the population in the water and additional low‐level flights to estimate the proportion of the hauled‐out population in groups too small to be detected in the infrared imagery. We believe that this approach offers the potential for obtaining reliable population estimates for walruses and other ice‐associated pinnipeds.

Testing antimicrobial cleaner efficacy on gypsum wallboard contaminated with Stachybotrys chartarum - Marc Y. Menetrez; Karin K. Foarde; Tricia D. Webber; Timothy R. Dean; Doris A. Betancourt (Environmental Science and Pollution Research, 2007)